Westside saints : a novel - Akers, W. M. (Harper Voyager, an imprint of HarperCollinsPublishers, 2020)
"Return to a twisted version of Jazz Age New York in this follow up to the critically acclaimed fantasy Westside, as relentless sleuth Gilda Carr's pursuit of tiny mysteries drags her into a case that will rewrite everything she knows about her past. Six months ago, the ruined Westside of Manhattan erupted into civil war, and private detective Gilda Carr nearly died to save her city. In 1922, winter has hit hard, and the desolate Lower West is frozen solid. Like the other lost souls who wander these overgrown streets, Gilda is weary, cold, and desperate for hope. She finds a mystery instead. Hired by a family of eccentric street preachers to recover a lost saint's finger, Gilda is tempted by their promise of 'electric resurrection', when the Westside's countless dead will return to life. To a detective this cynical, faith is a weakness, and she is fighting the urge to believe in miracles when her long dead mother, Mary Fall, walks through the parlor door. Stricken with amnesia, Mary remembers nothing of her daughter or her death, but that doesn't stop her from being as infuriatingly pushy as Gilda herself. As her mother threatens to drive her insane, Gilda keeps their relationship a secret so that they can work together to investigate what brought Mary back to life. The search will force Gilda to reckon with the nature of death, family, and the uncomfortable fact that her mother was not just a saint, but a human being."--Provided by publisher.